PERBEDAAN HASIL BELAJAR MATEMATIKA SISWA YANG DIAJAR DENGAN PEMBELAJARAN LURING DANPEMBELAJARAN DARING DI SMP NEGERI 1 PALU: Differences In Learning Outcomes Of Online Teaching Students And Offline TeachingStudents At Smp Negeri 1 Palu - Putri, Risma Wati; Rizal, Muh.; Hasbi, Muh. (Universitas Tadulako, 2024)
This study aims to obtain information related to whether there are differences in students' mathematics learning outcomes between offline and online learning at SMP Negeri 1 Palu. The research method used in this study is the comparative method. The population in this study were all grade VII students of SMP Negeri 1 Palu with a total of 352 students. The research sample was grade VII students who carried out offline and online learning, with different samples but had the same level of academic ability. The sampling technique in this study was Purposive Sampling. The researcher took 32 class A students and 32 class B students, so the number of samples taken was 64 people. The data collection technique in this study was by taking mid-semester test scores on the material Linear Equations and Inequalities of One Variable in the 2021/2022 Academic Year obtained by students during online learning and mid-semester test scores on Linear Equations and Inequalities of One Variable in the 2022/2023 Academic Year obtained by students during offline learning. On condition that the material taught is equivalent during offline and online learning and students have the same level of academic ability. The collected data is then processed using t-test statistical analysis. Based on the data analysis obtained: (1). The results of learning mathematics during online learning obtained an average value of 71.94; (2). The results of learning mathematics during offline learning obtained an average value of 58.56; (3). Sig. value. (2-tailed) 0.00 <0.05. This means that H0 is rejected and Ha is accepted. So the results of the study show that there is a difference in the results of learning mathematics of students taught with offline learning and online learning.